2012
DOI: 10.1186/1477-7525-10-92
|View full text |Cite
|
Sign up to set email alerts
|

Review of patient-reported outcome measures in chronic hepatitis C

Abstract: BackgroundChronic hepatitis C (CHC) and its treatment are associated with a variety of patient-reported symptoms and impacts. Some CHC symptoms and impacts may be difficult to evaluate through objective clinical testing, and more easily measured through patient self-report. This literature review identified concepts raised by CHC patients related to symptoms, impacts, and treatment effects, and evaluated integration of these concepts within patient-reported outcome (PRO) measures. The goal of this work was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…The FSS showed excellent psychometric properties (internal consistency α = .94; test-retest reliability = .82, convergent validity with SF-36 vitality subscale r = − 0.76) in a multi-center clinical trial in chronic HCV infection [24]. It has been suggested that FSS is used as a patient reported-outcome measure in chronic HCV infection [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FSS showed excellent psychometric properties (internal consistency α = .94; test-retest reliability = .82, convergent validity with SF-36 vitality subscale r = − 0.76) in a multi-center clinical trial in chronic HCV infection [24]. It has been suggested that FSS is used as a patient reported-outcome measure in chronic HCV infection [5].…”
Section: Methodsmentioning
confidence: 99%
“…In qualitative studies, patients described fatigue as the most concerning symptom of their illness and in quantitative reports fatigue was the second most common patient-reported outcome measure of the infection [5]. In the presence of persistent fatigue, increased effort is required to maintain important social roles and activities.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Examples of the questions asked include “exercise brings on my fatigue” and “my fatigue is very debilitating”; a higher score indicates a higher degree of fatigue for all items [18]. The standard scoring for the FSS was used: the 9 items were averaged to produce an FSS total score that ranges from 1 (no fatigue) to 7 (very severe fatigue) with scores calculated for all patients who answered at least half the FSS items.…”
Section: Methodsmentioning
confidence: 99%
“…PROMIS also features an Assessment Center, a free, online data collection tool that allows researchers to create study-specific websites, capture data electronically from patients, verify data integrity, store protected health information, and export to statistical software (http://www.assessmentcenter.net/). The development of new PRO measures specifically for HCV and antiviral therapy is burgeoning and warrants consideration for future PRO studies as well 10, 11 .…”
mentioning
confidence: 99%